1987
DOI: 10.1139/y87-299
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of N-methyl-D-aspartate (NMDA) evoked increases in cerebellar cGMP and striatal ACh release by phencyclidine (PCP) receptor agonists; evidence for possible allosteric coupling of NMDA and PCP receptors

Abstract: A comparison was made of the actions of phencyclidine receptor agonists and N-methyl-D-aspartate (NMDA) receptor antagonists in two well-defined neurochemical test systems. These included (i) [3H]acetylcholine release from striatal cholinergic interneurons in vitro, a system known to be positively modulated by corticostriatal excitatory amino acid inputs in vivo; and (ii) cerebellar cGMP levels in vivo, an indicator of cerebellar Purkinje cell activity, which is also modulated by excitatory amino acid inputs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Several studies have demonstrated a tight functional coupling between NMDA receptors and PCP recognition sites by receptor autoradiographic, behavioral, electrophysiological, and neurochemical lines of evidence (Lehmann and Scatton, 1982;Anis et al, 1983;Greenamyre et al, 1984;Snell and Johnson, 1986;Compton et al, 1987;Lodge et al, 1987;Loo et al, 1987;Wood et al, 1987Wood et al, , 1989aBennett et al, 1988). Such functional coupling between the NMDA receptors and PCP recognition sites results in antagonism of responses mediated by the NMDA receptor complex by PCP ligands in a noncompetitive manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated a tight functional coupling between NMDA receptors and PCP recognition sites by receptor autoradiographic, behavioral, electrophysiological, and neurochemical lines of evidence (Lehmann and Scatton, 1982;Anis et al, 1983;Greenamyre et al, 1984;Snell and Johnson, 1986;Compton et al, 1987;Lodge et al, 1987;Loo et al, 1987;Wood et al, 1987Wood et al, , 1989aBennett et al, 1988). Such functional coupling between the NMDA receptors and PCP recognition sites results in antagonism of responses mediated by the NMDA receptor complex by PCP ligands in a noncompetitive manner.…”
mentioning
confidence: 99%
“…The paradoxical biochemical effects of tiletamine (vide supra) led us to examine the effects of tiletamine on cerebellar cyclic GMP (cGMP) levels (in the mouse and rat) and behavior (in the rat), two well-characterized NMDA-coupled PCP recognition site-mediated responses (Wood et al, , 1987(Wood et al, , 1989aContreras et al, 1986;Compton et al, 1987), and effects on rat pyriform cortex DA metabolism release, a response mediated by the NMDA-uncoupled PCP recognition sites (Wood and Rao, 1989a;Rao et al, 1990a,b), to determine whether tiletamine interacts differentially with these two subpopulations of PCP recognition sites. We have also characterized tiletamine in several in vitro radioreceptor assays to determine the receptor specificity.…”
mentioning
confidence: 99%
“…Numerous attempts have been made to identify drugs which might either (a) mimic PCP in blocking the neurotoxic effects of glutamate or (b) antagonize the effects of PCP and thus constitute potential antipsychotic agents [Bakshi and Geyer 1995;Corbett et al 1995;Deutsch et al 2002]. However, based upon the prevailing hypothesis that the PCP receptor is located within the N-methyl-D-aspartate (NMDA) receptor-gated ion channel (Wood et al 1987;Javitt et al 1994;O'Donnell and Grace 1998), it is difficult to conceptualize a drug able to exclude PCP from its receptor without itself blocking the channel and thus mimicking the behavioral effects of PCP. Nonetheless, numerous drugs have been reported to diminish psychomotor activation by PCP (Maurel-Remy et al 1995;Klamer et al 2005;Podhorna and Didriksen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Irifune et al, have also demonstrated that ketamine has an indirect dopaminergic agonistic action [1]. The dopaminergic and NMDA systems have pivotal roles in the modulation of the presynaptic Ach release in the striatum [4,5]. In fact ketamine is known to inhibit Ach release in the striatum of rodents through the dopaminergic activating action and/or the antagonistic action on the NMDA receptors [5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the anesthetic action of ketamine is believed to be antagonism of the N-methyl-D-aspartate (NMDA) receptors. Several classes of the NMDA antagonists are known to reduce Ach release [5]. Ketamine may alter the regulatory mechanisms of mAchRs by inhibiting presynaptic Ach release, especially if ketamine is chronically or repeatedly administered.…”
Section: Introductionmentioning
confidence: 99%